Fuzzy logic with engineering applications - Ross, Timothy J. (John Wiley, 2010)
This new edition of a classic text has been updated with the latest advances in the area of fuzzy logic. It introduces new material on expansions of the MLFE method using genetic algorithms, cognitive mapping, fuzzy agent-based models and total uncertainty.